M(II)(H2O)2 (5, 5′-dimethyl-2, 2′-bipyridine)(fumarato) [M = Co and Zn] complexes bearing a unique distorted trigonal-prismatic geometry and displaying 2D supramolecular structures. (4th November 2015) - Téllez-López, Antonio; Jaramillo-García, Jonathan; Martínez-Domínguez, Rogelio; Morales-Luckie, Raúl A.; Camacho-Lopez, Miguel A.; Escudero, Roberto; Sánchez-Mendieta, Víctor
Graphical abstract: Unique distorted trigonal-prismatic Co and Zn complexes bearing aqua and η 1 :η 1 – fumarato ligands exhibiting 2D-supramolecular arrays. Abstract: Novel M(II)(H2 O)2 (dbpy)(fum) complexes, M = Co (1 ) and M = Zn (2 ); where: dbpy = 5, 5′-dimethyl-2, 2′-bipyridine, fum = fumarato; were obtained by simple one-pot solution reactions at ambient conditions, and structurally characterized by elemental analysis, IR spectroscopy and X-ray single crystal diffraction. In both complexes, the Co(II) and Zn(II) ions exhibit an uncommon six-coordinated distorted trigonal-prismatic geometry, especially for complexes having mono-dentate and bi-dentate innocent ligands. These are the first examples of metaprism complexes with aqua ligands in their coordination spheres. Moreover, the η 1 :η 1 non-bridging coordination mode of fumarato ligand appears for the first time in these type of mononuclear complexes. In addition, the solid-state self-assembly of the mononuclear structures of1 and2, mainly throughout hydrogen bonding, give rise to 2D supramolecular wrinkle-sheet type frameworks. These extended structures seem to be the driving force for the unusual coordination geometry obtained in both complexes. Magnetic properties measurements reveal that complex1 exhibits weak antiferromagnetic ordering with θ ( C–W ) = −14 K and an E 1 = 0.24 cm −1 according to Curie–Weiss model and Rueff phenomenological approach, respectively; whereas, complex2 displays blue fluorescence in the solid-state.